New views of the human NK cell immunological synapse: recent advances enabled by super- and high-resolution imaging techniques - Mace, Emily M.; Orange, Jordan S. (Frontiers in Immunology, 2013)
Imaging technology has undergone rapid growth with the development of super resolution microscopy, which enables resolution below the diffraction barrier of light ( 200 nm). In addition, new techniques for single molecule imaging are being added to the cell biologist’s arsenal. Immunologists have exploited these techniques to advance understanding of NK biology, particularly that of the immune synapse. The immune synapse’s relatively small size and complex architecture combined with its exquisitely controlled signaling milieu have made it a challenge to visualize. In this review we highlight and discuss new insights into NK cell immune synapse formation and regulation revealed by cutting edge imaging techniques, including super resolution microscopy and high resolution total internal reflection microscopy and Förster resonance energy transfer.